Factors Influencing Intention and Decision to Visit Gadang Clock Tower Tourist Object in Bukittinggi, West Sumatra - Marlina, Winny Alna; Surbakti, Eliza Ellen; Agus, Alfian (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives:  The objective of this study is to contribute to the existing body of literature regarding the decision-making process of visiting the Gadang Clock Tower tourist attraction. This will be achieved by examining aspects like travel motivation, electronic word-of-mouth (EWOM), eco-destination image, and intention to visit. There exists a dearth of scholarly research on Gadang clocks, particularly about their significance within eco-destinations. Consequently, there is a pressing need for further investigation in this area.Methodology: The data utilized in this study was obtained via a survey of tourists who were visiting the Clock Tower in Bukittinggi. The SEM is utilized in the assessment of validity, reliability, cross-loading, and t-statistics.Finding: The study found that the influence of electronic word-of-mouth and eco-destination images on tourists' intentions and visiting decisions at the Gadang Clock Tower was positive and significant. Therefore, it can be inferred that these elements play a crucial role in enhancing visitors' intentions and decisions.Conclusion: If the Clock Tower possesses a favorable eco-destination image, it is likely to attract a higher influx of tourists. Electronic word-of-mouth (e-WOM) has a substantial impact in influencing individuals' levels to encounter the clock tower. The number of visitors expressing an intention to revisit the Gadang Clock is expected to increase if they have a remarkable and memorable experience on their initial visit. Furthermore, the act of visiting the Clock Tower exerted a substantial impact on their subsequent inclination to revisit it.